Unveiling triple bottom line's influence on business performance - Elisabete Nogueira; Sofia Gomes; João M. Lopes (Discover Sustainability)
Abstract Addressing environmental, social, and economic challenges has become a pressing global priority. The Triple Bottom Line (TBL) framework offers a holistic approach for evaluating corporate performance by integrating economic, environmental, and social perspectives. Despite its increasing adoption in both managerial and academic research, there remains a significant gap in understanding how the TBL framework influences business performance. To address this, the study conducts a bibliometric review of 207 publications from the Web of Science database. The review highlights the multifaceted impact of practices linked to the TBL dimensions on business performance while introducing the TBL Influence on Business Performance model. This model provides valuable insights into how businesses can effectively apply TBL principles to address socio-environmental challenges, foster innovation, and achieve sustained long-term performance. The findings contribute valuable theoretical and practical insights into how organizations can utilize TBL principles to strengthen resilience, innovation, and performance in the face of global socio-environmental challenges.